Butser Ancient Farm 2020 - Trevor Creighton (EXARC Journal, 2020)
Butser Ancient Farm has been at the forefront of experimental archaeology in Britain for more than 45 years. The pioneering work of its first director Dr Peter Reynolds in the evaluation of Iron Age structures and agriculture demonstrated beyond doubt the importance of experiment in archaeology in the UK and international experimental archaeology work. Butser Ancient Farm has focused particularly on archaeological reconstructions in more recent years, while both expanding and extending its scope beyond the Iron Age. The expansion began in 2003 with a Romano-British villa and has proceeded since 2014 to encompass the Neolithic and Anglo-Saxon periods. The site now has 12 major experimental buildings with numerous ancillary structures. The pace of expansion has necessitated the careful consideration of strategies to document, record and store key information about the archaeology from which the buildings were derived; the rationale and processes involved in their construction; practical and financial aspects of construction; interpretation and usage of the buildings; recording of subsequent phases of research including the documentation of their decay and of archaeology derived from their demise. Beyond the obvious material considerations, we are also developing methodologies for capturing the experiential impressions of those involved in the construction and later use of the buildings. Key to this process is our newly implemented digital storage file protocol, the objective is to allow users to store data with consistency, clarity, ease of use and organised in such a way that search and retrieval is intuitive and efficient. This brief paper aims to provide an illustration of the system with the ambition of contributing to the discussion of implementing a system to store and share information on a broad, consistent, international platform.